Conocimientos y actitudes hacia la prevención de accidentes en el hogar en madres de la I.E.I. N° 366 del Centro Poblado de Rumococha Iquitos – 2024 - Coral Coral, Nardy (2025)
The main objective was to determine the relationship between knowledge and attitudes toward home accident prevention among mothers at Early Childhood Education Institution No. 366 in the Rumococha Population Center, Iquitos, 2024. A quantitative approach was used with a non experimental, descriptive, cross-sectional, correlational design. The sample consisted of 95 mothers. The methodology used was a survey and home visits, while the instruments used were a knowledge questionnaire and a Likert scale for attitude. The results were: 93.7% of mothers had low knowledge, followed by 6.3% with high knowledge; 61.1% of mothers had a positive attitude, followed by 38.9% with a negative attitude. The relationship between the level of knowledge and mothers' attitudes toward home accident prevention revealed a statistically significant relationship (X2 = 4.086; df = 1; p = 0.043). Concluding that adequate knowledge fosters positive attitudes.